Chris Hani (left, with sunglasses) and Klaas de Jonge (right) at an ANC rally in Lady Frere, South Africa - Boersma, Pieter
Chris Hani (left, with sunglasses) and Klaas de Jonge (right) at an ANC rally in Lady Frere, South Africa.